From Institutions to Financial Development and Growth: What Are the Links? - Andrés Fernández Martin; César E. Tamayo (Inter-American Development Bank (IDB), 2015)
This paper presents an integrated overview of the literature linking institutions, financial development and economic growth. From the large body of research on institutional development, the paper first selects those contributions that make it possible to study the role of institutional arrangements in ameliorating/worsening the information frictions and transaction costs that characterize the development of financial markets. The paper then investigates the theoretical mechanisms by which these specific frictions affect economic growth and presents the stock of empirical evidence quantifying the impact of institutions on growth through financial development.
hdl:11319/6867
Keywords: G14; G28; G38; O16; O43; 330; Financial development; Financial frictions; Property rights; Contract enforcement; Transaction costs; Institutions; Economic growth